TANTANGAN PETANI CABAI DALAM MENCARI BURUH PANEN DI DESA PAREPEI, KABUPATEN MINAHASA - Romi Mesra; Rio Risjal Sandag; Sandi Adis Dien; Tasya M. Tambuwun; Kurnia Sengkey; Sintia Kumolontang; Gabriela C. Timporok (Labor Program Studi Pendidikan Sosiologi, 2022)
This study aims to determine the challenges of the chili farming community in Parepei Village, in meeting the need for chili harvesting laborers so that the chili farmers in Parepei Village hire or seek harvest workers from outside the village, in fulfilling the needs of chili harvesting from farmers. The research method used is qualitative research by collecting observation data and direct interviews with several informants. The general results of the study show that the challenges of chili farmers in finding harvest laborers are because there are still many people who have the prestige to work as chili labor farmers, there are still many people who are embarrassed to work as chili labor farmers, many people prefer to work outside the village, lack of trust chili farmers to young people